Framing teacher education: Conceptions of teaching, teacher education, and justice in Chilean national policies - Fernández, M. Beatriz (Education Policy Analysis Archives, 2018)
Chile shows high inequity and socioeconomic stratification in both K-12 education and teacher preparation. Drawing on the notion of frames, this critical policy analysis examines how teaching, teacher education, and justice were conceptualized in Chile’s teacher preparation policies between 2008-2015. It also analyzes the narrative stories implicit in these policy documents. Analysis of the documents shows that national policies emphasize a content knowledge for teaching and teacher education and conceptualize justice as an issue of access to quality teachers. These approaches to teaching, teacher education, and justice are similar to predominant discourses in countries like the US. However, Chilean national policies are promoted using a narrative of development instead of the narrative of decline or crisis usually used in developed countries. These findings contribute to the understanding of national teacher education policies and their connection to the process of policy borrowing. The paper shows both the particularities of frames and narratives used in teacher education policies in developing countries like Chile and their similarities to those in countries that implement neoliberal policies in teacher education.